Design of Automatic Organic Fertilizer Processing Tools by Utilizing the Internet of Things (IOT) as a Monitoring System - Fadhila Desti Rahmaniar; Jon Endri; Irma Salamah (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2023)
This paper aims to design an automatic organic fertilizer processing tool by utilizing the Internet Of Things (IOT) as a monitoring system. The proposed tool system aims to make it easier to sort organic waste or inorganic waste which can then also automatically process organic waste into organic fertilizer. The method used is a literature survey conducted to solve relevant problems. At this stage, a data collection survey is carried out by utilizing previous research sources from books, journals, and the internet. We used this literature review to enable us to update the tool from previous research. The proposed system uses ESP 32 module as a microcontroller that can connect to WiFi. In addition, it has also been introduced in the Internet of Things (IOT) as an automatic monitoring system for organic fertilizer processing plants. Garbage download information is sent via the internet and returned to the Android application. However, in this study, one application, namely WhatsApp, was used. Garbage has long been a social problem, especially in big cities, polluting the environment, endangering public health, and reducing environmental aesthetics. Therefore, waste management is important to minimize the negative impact of waste. Finally, the research results obtained can be useful as technological development in the future of automatic organic waste processing equipment.